Transformerless Step-Up Inverter Based On Switched-Capacitor Converter Technology - Neilor Colombo Dal Pont; Gierri Waltrich; Telles Brunelli Lazzarin (Eletrônica de Potência)
In this paper the integration between a voltage source inverter (VSI) and a switched capacitor converter (SCC) is proposed to generate a sinusoidal waveform with a double peak voltage value at the converter output terminal, without the use of a transformer or a dc-dc boost converter. The novel structure (VSI-SCC) is designed as a transformerless step-up inverter with linear gain. VSI and SCC models are individually characterized to integrate both structures in only one model. To validate the theoretical analysis a prototype was designed for a power of 1 kW, considering a dc input voltage of 200 V and an ac output voltage of 220 V (rms). In this prototype the VSI converter supplies 110 V (rms) to the SCC converter, and this converter step-up it to 220 V (rms). Furthermore, open and closed-loop control were also tested in the prototype reaching a maximum efficiency of 90%.